2022
DOI: 10.1039/d1tb02729h
|View full text |Cite
|
Sign up to set email alerts
|

Selection of CD133-targeted DNA aptamers for the efficient and specific therapy of colorectal cancer

Abstract: Tumor-targeted delivery of antitumor drugs is considered a promising strategy for improving chemotherapeutic efficiency and reducing the incidence of side effects. The development of tumor-targeted aptamers to accommodate drugs has...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In particular, a chimeric drug that is a CD133-targeted DNA aptamer combined with doxorubicin showed selective killing effect in human colorectal cancer HCT116 cells expressing CD133. The in vitro and in vivo results demonstrated the high therapeutic efficacy and low toxicity of this chimera [112]. Also, recent in vitro study has shown the effective use of Fc-optimized antibodies against CD133 to induce natural killer (NK) cell reactivity [113].…”
Section: Cd133 As a Target Of Therapies Aimed To Eliminate The Most M...mentioning
confidence: 90%
“…In particular, a chimeric drug that is a CD133-targeted DNA aptamer combined with doxorubicin showed selective killing effect in human colorectal cancer HCT116 cells expressing CD133. The in vitro and in vivo results demonstrated the high therapeutic efficacy and low toxicity of this chimera [112]. Also, recent in vitro study has shown the effective use of Fc-optimized antibodies against CD133 to induce natural killer (NK) cell reactivity [113].…”
Section: Cd133 As a Target Of Therapies Aimed To Eliminate The Most M...mentioning
confidence: 90%
“…They are not only able to penetrate into the solid tumor better than antibodies but are also internalized in the cell by receptor-mediated endocytosis [ 138 ]. Aptamers can be used as a component in sensor detection systems [ 139 ] and in vectors for drug delivery to cancer stem cells [ 140 , 141 , 142 , 143 , 144 ]. In addition to aptamers, peptides capable of specific binding to CD133 can be selected using phage display peptide libraries and the systematic evolution of ligands by exponential enrichment [ 145 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%